Oxford handbook of psychiatry - Semple, D. David (Oxford Medical Handbooks, 2019)
This new fourth edition of the Oxford Handbook of Psychiatry is the essential, evidence-based companion to all aspects of psychiatry, from diagnosis and conducting a clinical interview to management by subspecialty. Fully updated to reflect changes to the legislature and classification of psychiatric disorders, and with coverage of the anticipated ICD-11 coding, this Handbook provides the latest advances in both clinical practice and management today. As in previous editions, the Handbook is indexed alphabetically by ICD-10 and DSM-5 codes,as well as a list of acute presentations for quick access in emergency situations. The practical layout helps the reader in making clinical diagnosis, and suggested differential diagnosis makes this title an invaluable guide to provide reassurance to health professionals when dealing with psychiatric issues. With a new chapter on Neuropsychiatry and a re-written section on gender dysphoria to reflect the biological and cultural developments in understanding and research since the previous edition, and filled with clinical observations, guidance, and commentary that reflects the authors' practical experiences of working in psychiatry, this Handbook is the indispensable guide for all trainee and practising psychiatrists.